2013
DOI: 10.1227/neu.0b013e318270d02c
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Robotics

Abstract: Even though robotic technology holds great potential for performing spinal surgery and advancing neurosurgical techniques, it is of utmost importance to establish its practicality and to demonstrate better clinical outcomes compared with traditional techniques, especially in the current cost-effective era. Several systems have proved to be safe and reliable in the execution of tasks on a routine basis, are commercially available, and are used for specific indications in spine surgery. However, workflow, usabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 251 publications
(110 citation statements)
references
References 29 publications
4
106
0
Order By: Relevance
“…Full text screening of the remaining 22 articles led to the exclusion of a further 17 articles. In all, 5 articles were identified that satisfied our inclusion criteria, comprising two randomized controlled trials (of which one reported preliminary findings), one prospective cohort, one retrospective cohort, and one cadaveric study (Table 1) [9,11,17,18,20]. A total of 1,308 pedicle screws were reported-729 using robot-assistance, and 579 using fluoroscopy-guidance.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Full text screening of the remaining 22 articles led to the exclusion of a further 17 articles. In all, 5 articles were identified that satisfied our inclusion criteria, comprising two randomized controlled trials (of which one reported preliminary findings), one prospective cohort, one retrospective cohort, and one cadaveric study (Table 1) [9,11,17,18,20]. A total of 1,308 pedicle screws were reported-729 using robot-assistance, and 579 using fluoroscopy-guidance.…”
Section: Resultsmentioning
confidence: 99%
“…The other randomized controlled trial by Roser et al [18] reported preliminary findings of a three-arm study comparing fluoroscopy-guided, image-guided (BrainLab VectorVision 2, Feldkirchen, Germany), and robot-assisted pedicle screw placement. The study aims to enroll 90 patients with 4 screws per patient, but has so far recruited 37 patients, with fewer patients undergoing fluoroscopy-guided (n = 10) or image-guided (n = 9) surgery than robot-assisted (n = 18) pedicle screw placement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations